Lutte de voisinage et patrimonialisation d’espaces naturels résiduels à Madrid - Elia Canosa Zamora; Ángela García Carballo (VertigO, 2013)
The city of Madrid has historically shown a clear disregard for the waterways and their heritage value has been swallowed up by urban development. However, some fragments of this nature neglected, associated with stream valleys, have been finally recognized as urban parks, the highest expression of nature in the city. The aim of this research is to illustrate the heritage process of these places, emphasizing the role of neighborhood's struggles during the period 1975-1990. Finally, we expose the expensive, unsustainable and media orientation design of the last urban parks built on the site of ancient streams.